Edukasi Reproduksi Ternak Berbasis Sains: Penguatan Kapasitas Peternak Kambing dalam Perkawinan Silang Multibangsa di Desa Setanggor - Maskur; Musanip; Lalu Muhammad Kasip; Tapaul Rozi; Muhammad Muhsinin (Universitas Mataram, 2026)
This community service program aimed to strengthen the capacity of smallholder goat farmers in Desa Setanggor, Central Lombok, through science‑based education on animal reproduction and the implementation of multibreed crossbreeding techniques. Local goat productivity in the village remains low due to limited genetic potential, suboptimal feeding practices, and restricted access to reproductive technologies. The program was designed using a participatory, andragogical approach that combined lectures, discussions, demonstrations, hands‑on practice, and field mentoring. Core activities included training on basic reproductive physiology, principles of multibreed crossbreeding and selection of superior bucks, feeding management using local feed resources, herd health, simple performance and financial recording, as well as introductory training on branding and digital marketing. Farmer knowledge was assessed through pre‑ and post‑tests, while changes in farm practices were monitored qualitatively through observation and follow‑up visits. The results show clear improvements in farmers’ understanding of reproductive concepts and crossbreeding, followed by the initial adoption of more targeted mating plans, more regular feeding and basic health practices, and the use of simple herd and cash‑flow records. Farmers also began to utilize social media to promote their goats and expand market reach. Overall, the program demonstrates that science‑based reproductive education, when integrated with managerial and marketing support, can effectively enhance farmer capacity and support sustainable improvements in the productivity and competitiveness of local goats, in line with the Merdeka Belajar–Kampus Merdeka policy.